In vitro characteristics of an airway barrier‐disrupting factor secreted by Staphylococcus aureus. Issue 2 (15th November 2018) - Murphy, Jae; Ramezanpour, Mahnaz; Drilling, Amanda; Roscioli, Eugene; Psaltis, Alkis James; Wormald, Peter‐John; Vreugde, Sarah
Abstract : Background: Staphylococcus aureus is a major contributor to the pathophysiology of chronic rhinosinusitis (CRS). Previous research has shown that S. aureus –secreted products disrupt the airway barrier. Methods: S. aureus ATCC 13565 and 25923 strains were grown at exponential, postexponential, and stationary phases. Microbial conditioned media (CM) was collected from the cultures and ultrafiltered (UF). Liquid chromatography–electrospray ionization tandem mass spectrometry (LC‐ESI‐MS/MS) was performed on the UF‐CM. UF‐CM was subjected to heat and protease treatment, size fractionation, and ultracentrifugation (UC) separation. Human nasal epithelial cells grown at air‐liquid interface (HNEC‐ALI) cultures were exposed to purified alpha hemolysin (Hla), staphylococcal enterotoxin A (SEA), lipoteichoic acid (LTA), and UF‐CM. Barrier function outcomes were measured by transepithelial electrical resistance (TEER) and apparent permeability (Papp). UC fraction exposed cultures were subjected to immunofluorescence microscopy for tight junction (TJ) protein zonula occludens‐1 (ZO‐1). Results: LC‐ESI‐MS/MS identified 107 proteins, with Hla being most abundant. Hla, SEA, and LTA did not alter the HNEC‐ALI barrier as measured by TEER or Papp. Barrier disruption caused by UF‐CM peaked in the postexponential phase, was sensitive to heat and protease treatment, >30‐kDa in size, and enriched in the UC fraction. HNEC‐ALI exposed to UF‐CM and UC demonstrated loss of ZO‐1 localization. Conclusion: These results suggest that the S. aureus factor responsible for TJ disruption in HNEC‐ALI cultures is either a protein‐macromolecule or a combination of secreted factors. The product is enriched in the UC fraction, suggesting it is associated with large structures such as membrane components or vesicles.